Strategic plan of Grupo GEA for sustainable education area - Sovero Zamudio, Liliana Cristina (2015)
The present paper propose the strategic plan for the non-profit organization Grupo GEA, more specifically, for its sustainable education area, which has as main product the Buena Voz program. The proposed strategic plan goes from year 2015 to 2018. The deployment of the plan was made by using the strategic process proposed by D’Alessio (2013). In the case of Grupo GEA, the need of developing this plan started when it becomes difficult for the organization to get funds for the Buena Voz program. Therefore, the strategic plan has as objective strengthen the continuity of fundraising. Throughout the strategic plan, the vision, mission, values and code of ethics were reviewed. The final vision defined was, to be the first NGO in Peru who innovate integrated projects for sustainable development and promote fair relationships between society, economy, and environment, while fostering the country to be in-line with the latest Sustainable Development Goals (SDG) by 2020. Specifically for sustainable education area, to be the first referent in Peru of non-formal education, to develop soft skills of leadership among vulnerable youth. In order to achieve the vision, and external and internal analysis was made, followed by the definition of the interests of the organization, its potential, cardinal principles, five long-term objectives, which will ensure the achievement of the vision. To achieve this, seven strategies were designed; and with them, 11 short-term objectives, their resources, policies, and other implementation guidelines. As a last stage a balance scorecard with goals, indicators, activities and measurement was developed in order to control the evolution of the strategic plan and made any adjustments is needed. Finally, it is concluded that if Grupo GEA follows the proposed strategic plan, they will be able to successfully relaunched the Buena Voz program, in addition, full commitment from the entire organization is key.